Sudirman Street: Interaksi Budaya di Ruang Publik - Zera Edenzwo Subandi; Surianto Surianto; Kho, Gerson Ralph Manuel; Samuel Christian Widjaja (SENTRI: Jurnal Riset Ilmiah, 2025)
This research examines the dynamics of cultural interaction between tourists and local communities in the culinary public space of Sudirman Street, Bandung, within the framework of intercultural communication. Sudirman Street has emerged as a new cultural space and serves as a symbol of a “melting pot,” where diverse cultural and religious backgrounds converge amidst the dominance of religious values in Bandung society. The aim of this research is to understand how social symbols construct meaning and relationships among individuals through public interactions. A qualitative approach grounded in the sociocultural tradition is employed, utilizing field observations, interviews, and documentation. The findings indicate that, despite religious norms concerning halal and non-halal practices, social behavior at Sudirman Street reveals a flexible negotiation of meaning among individuals, informed by personal understanding (mind) and self-identity (self), as conceptualized in George Herbert Mead’s theory of symbolic interactionism. The study reveals that tolerance, cultural compromise, and symbolic adaptation are essential for fostering social harmony within this public space. These findings suggest that culinary tourism is not merely an economic activity but also a site for cultural dialogue that reflects the level of tolerance within a city. Through Sudirman Street, Bandung demonstrates its potential to serve as a model of inclusive public space that accommodates cultural and religious diversity.